Penguatan Performa Sepak Takraw, Manajemen Diri dan Motivasi Belajar Siswa SKO Riau - Zulkifli, Zulkifli; Yani, Ahmad; Putra, Elpri Darta; Gunawan, Arzami; Azriqiansayah, Muhammad (Universitas Pahlawan Tuanku Tambusai, 2026)
This community service program aims to strengthen sepak takraw performance, self-management, and learning motivation of students at the Riau Special Sports School (SKO). This activity was motivated by the need for student athlete development that focuses not only on improving sports performance but also on developing self-management and learning motivation to support balanced sports and academic achievement. The community service method was implemented through structured practice-based sepak takraw performance training, self-management mentoring, and strengthening learning motivation through an educational and reflective approach. The activity included planning, implementation, and evaluation stages. The results of the community service program demonstrated improvements in the quality of sepak takraw performance, self-management skills, and student learning motivation. This activity is important as a holistic development model for SKO students in achieving sustainable sports and academic achievement.